Chapter I primi due secoli della storia di San Miniato - Contessa, Maria Pia (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The essay sketches the activity of Abbot Ubertus from San Miniato, who rebuilt the church and worked to promote the monastic complex as a spiritual pole, a cultural centre, and a shelter for poor and pilgrims, condolidating monastic estates in the nearby country of Ripoli, where he acquired properties thenceforward important for monks' economy and social relationships. During the XIIth century, like many other Florentine religious institutions, San Miniato cooperated in the urbanization, favouring accomodations of people coming from the south of Florentine territory in buildings located along the left Arno riverside.